Effects of practitioner’s experience on the clinical performance of ultrasound-guided central venous catheterization: a randomized trial - Hyun-Kyu Yoon (Nature Portfolio, 2021)
Abstract We investigated whether two needle insertion techniques for ultrasound-guided internal jugular vein (IJV) catheterization differ in the number of needling attempts and complication rate between inexperienced and experienced practitioners. A total of 308 patients requiring IJV catheterization were randomly assigned into one of four groups: IJV catheterization performed by inexperienced practitioners using either Seldinger (IE-S; n = 78) or modified Seldinger technique (IE-MS; n = 76) or IJV catheterization performed by experienced practitioners using either Seldinger (E-S; n = 78) or modified Seldinger technique (E-MS; n = 76). All catheterizations were performed under the real-time ultrasound guidance. The number of needling attempts was not significantly different between the two techniques within each experience group (between IE-S vs. IE-MS P = 0.550, between E-S and E-MS P = 0.834). Time to successful catheterization was significantly shorter in the E-S group compared to E-MS group (P < 0.001) while no significant difference between IE-S and IE-MS groups (P = 0.226). Complication rate was not significantly different between the two techniques within each experience group. Practitioner’s experience did not significantly affect the clinical performance of needle insertion techniques during ultrasound-guided IJV catheterization except the time to successful catheterization. Regarding the number of needling attempts and complication rate, both techniques could be equally recommended regardless of practitioner’s experience. Trial registration: clinicaltrials.gov (https://clinicaltrials.gov/ct2/show/NCT03077802).